A study on the role of polypropylene fibers and silica nanoparticles on the compression properties of silicone rubber composites as a material of finger joint implant. Issue 1 (2nd January 2017) - Ziraki, Sahar; Zebarjad, Seyed Mojtaba; Hadianfard, Mohammad Jafar
ABSTRACT: In this study, different contents of SiO2 nanoparticles and polypropylene fibers were added to silicone rubber matrix as a material of finger joint implants and mechanical properties of these composites were investigated before and after being soaked in simulated body fluid. Results of compression test revealed that compression stress of silicone rubber by addition of the 2 wt% silica and 2 wt% PP fibers increased from 0.98 to 1.9 and 2.37 MPa, respectively. These stresses decreased after being soaked in SBF and water absorption results proved this. Increasing silica contents caused an increase in water absorption while increasing PP fibers showed contrary behavior. GRAPHICAL ABSTRACT: